Feasibility Study for The Proposed Poultry Feed Manufacturing Plant by PT. X: Implementing Agricultural Commodity Downstreaming in Gresik, East Java - Rahmah, Mutiara Julia; Oetomo, Dedy Setyo; Ramdhani, Rizky (Journal of Social Science and Business Studies, 2025)
This study aims to analyze the feasibility of establishing a poultry feed factory by PT. X in Gresik, East Java, as part of Indonesia’s national agricultural downstreaming strategy. The feasibility study evaluates multiple aspects, including technical and technological considerations, raw material availability, and market and marketing potential, particularly for both domestic and export opportunities. The assessment also includes the estimation of local raw material requirements and the identification of appropriate equipment and technology for the factory’s operations. From a market perspective, the study evaluates current and projected demand for poultry feed products, supported by the growing livestock sector and increasing export prospects. From a financial standpoint, the project shows strong viability. Key financial indicators demonstrate positive outcomes: the Net Present Value (NPV) is greater than zero, the Internal Rate of Return (IRR) exceeds the prevailing loan interest rate, and the Payback Period falls within an acceptable and efficient timeframe. These indicators collectively reflect the project’s potential to generate sustainable profits and recover the initial investment within a reasonable period. Considering all evaluated aspects, the development of PT. X's poultry feed factory in Gresik is deemed feasible in terms of technical implementation, market potential, and financial returns. Moreover, the project aligns with national objectives to enhance agricultural value chains through industrial downstreaming, optimize the use of local resources, and contribute to regional and national economic development. As such, the proposed investment not only supports agribusiness growth but also reinforces broader economic resilience and food security initiatives in Indonesia.